Socio-ecological analysis of the eutrophication in Chesapeake Bay, USA - Leyva Ollivier, María Esther; Newton, Alice; Kelsey, Heath (Frontiers in Marine Science, 2023)
This study is a social-ecological analysis of eutrophication in the Chesapeake Bay, United States of America (USA). It uses an expanded DPSIR framework (Drivers/Pressures/State/ Impacts/Responses) methodology to analyze the issue. In addition, a typology of the social actors and stakeholders in the socio-economic part of the system is identified. These stakeholders include residents, agriculturists, fishers, real estate developers, tourism operators, scientific researchers, and state and federal regulators. The framework results found that the Drivers are food security, housing, economic development, recreation pursuits, a sense of belonging, and population growth. These result in human Activities such as land and coastal change for development, coastline changes for fisheries, urban or suburban development, burning fossil fuels, and agricultural fertilization. The activities exert Pressures such as wastewater discharge, runoff from cleared land, atmospheric deposition (NOx), nutrient input, decreased tidal vegetation, and overfishing of filter feeders. These alterations change the State of the environment and its resilience by increasing the duration and areal extent of hypoxia, turbidity, and change in nutrient ratios. This also causes ecosystem changes, such as a decrease in wildlife diversity, and affects ecosystem services, such as decreasing nutrient buffering. The health of Chesapeake Bay benefits all stakeholders and wildlife, so the reduction of ecosystem services results in Impacts on society’s welfare and well-being, the economy, and environmental justice. Examples are decreased fishery yields and poorer water quality, affecting aesthetics, tourism, and ultimately human health. The governance Response to the degradation of the Chesapeake Bay and main management Measures has been the formation of the Chesapeake Bay Program, which has developed several agreements to improve water quality. The Chesapeake Bay Foundation, Chesapeake Progress, and Report Cards are accountability tools to observe and communicate the management project results or enforce state laws. The current management shows promising results, but further efforts are required to improve the water quality. Using various management options may bridge this gap to benefit all stakeholders. The main conclusion is that, although eutrophication is a complex problem, there is a scientific knowledge-base and a range of management options to restore the Chesapeake Bay.